DIAGNOSTIC ACCURACY OF THE WHO LABORATORY-BASED CARDIOVASCULAR RISK CHART IN DETECTING CARDIOVASCULAR DISEASE AT DR. SITANALA GENERAL HOSPITAL - Mulia; Marlin Brigita (Journal of Noncommunicable Diseases Prevention and Control, 2025)
Cardiovascular disease is the leading cause of death worldwide. The World Health Organization Cardiovascular Risk Chart (laboratory-based) was developed as a screening tool to estimate the ten-year risk of cardiovascular events. However, its validity in Indonesia has not been widely evaluated. This study aimed to evaluate the accuracy of the World Health Organization Cardiovascular Risk Chart (laboratory-based) and to analyze the relationship between several risk factors, including age, sex, smoking status, systolic blood pressure, total cholesterol level, and diabetes mellitus status, with the occurrence of cardiovascular disease. This quantitative study used a cross-sectional design with secondary data from outpatient medical records at Dr. Sitanala Central General Hospital from January 2024 to March 2025. A total of 210 respondents were included. Data were analyzed using univariate analysis, chi-square tests, and diagnostic tests using the receiver operating characteristic curve to determine the area under the curve, sensitivity, specificity, positive predictive value, negative predictive value, likelihood ratios, and overall accuracy. Among the respondents, 107 individuals (51 percent) were diagnosed with cardiovascular disease. The area under the curve was 0.564 (p = 0.107; 95 percent confidence interval: 0.487–0.642), indicating low discriminative ability. Sensitivity was 66.36 percent and specificity was 41.75 percent. Significant associations were found between sex, smoking status, and total cholesterol level with the occurrence of cardiovascular disease (p < 0.05). The World Health Organization Cardiovascular Risk Chart (laboratory-based) demonstrated low predictive ability for detecting cardiovascular disease in this population.